A polyurethane–chitosan brush as an injectable hydrogel for controlled drug delivery and tissue engineering. Issue 40 (26th September 2017) - Mahanta, Arun Kumar; Senapati, Sudipta; Maiti, Pralay
Abstract : Hydrogels and porous lyophilized hydrogels have been designed using a polyurethane brush with a chitosan backbone through grafting for controlled drug delivery. Abstract : Hydrogels and porous lyophilized hydrogels have been designed using a polyurethane brush with a chitosan backbone through grafting. The degree of substitution of grafting has been varied for controlled properties and has been confirmed by 13 C NMR, FTIR and UV-vis measurements. Surface modification of chitosan has been done to check the hydrophilic–hydrophobic balance which is reflected in their swelling behavior and contact angle. Porous interconnected three dimensional network structures with controlled size are observed by using a scanning electron microscope. Hydrogels or lyophilized hydrogels have sufficient mechanical strength and the brush like structure helps increase the fluidity as measured from the lesser viscosity under oscillatory shear as compared to pure chitosan and thereby the brush acts like a slipping agent. Sustained drug release is achieved using a brush copolymer as opposed to burst release noticed in pure chitosan. A controlled drug release phenomenon has been modeled both for hydrogels and lyophilized hydrogels following the Fickian diffusion ( n < 0.45). Excellent cytocompatibility of the brush copolymer has been verified through cell line studies using mouse embryonic fibroblast cells. Interestingly, the cells grow nicely within the pores of a graft copolymer while predominantly the usual cell growth on the surface is observed in the lyophilized hydrogel of chitosan indicating the effect of brush like modification on the chitosan backbone towards better cell proliferation. The developed brush copolymers have the ability to form hydrogels under physiological conditions at 37 °C through sol–gel transformation which makes them suitable to be used as injectable hydrogels as evidenced from the in vivo experiment using a rat model. Hence, the developed brush copolymers are promising as potential biomaterials for drug delivery and tissue engineering applications.